Towards small-x resummed parton distribution functions - Rottoli, L; Bonvini, M (International School for Advanced Studies, 2018)
We present preliminary results for fits of parton distribution functions (PDFs) which include the resummation of small-x logarithms at NLLx accuracy, performed in the NNPDF framework. We observe an improvement in the description of DIS data at small values of Bjorken x when resummation effects are included. The improvement is more marked when comparing NNLO+NLLx fits to NNLO ones, and is particularly noticeable for small-x and small-Q 2 HERA inclusive structure functions. The main effect of the resummation is an enhancement of the gluon and singlet PDFs at small-x, which persists at high scales.